Divorce Sues Through E-Court Process In The Binjai Religious Court in North Sumatera During The Covid-19 Pandemic - Muhammad Ridho Nasution; Sukiati Sukiati; Ramadhan Syahmedi Siregar (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2022)
The purpose of this study is to find out how the implementation of divorce lawsuits through the e-court at the Binjai Religious Court, the difference between filing an ordinary lawsuit and filing through an e-court, and the effectiveness of implementing a divorce lawsuit through the e-court at the Binjai Religious Court. This research is an empirical legal research, with a case study approach and a statutory approach. The data sources are primary and secondary data, the data collection techniques are observation, interviews and documentation. The results of the research are: First, the implementation of a lawsuit in the Binjai Religious Court in terms of registration through the e-court itself is of two kinds, namely advocates/legal entities and independent users. Second, the difference between an ordinary lawsuit and the submission through e-court is an ordinary lawsuit, a divorce suit is filed by the husband or wife or their proxies to the Court whose jurisdiction includes the defendant. Third, the effectiveness of the implementation of divorce lawsuits through e-court through the Binjai Religious Court of North Sumatra can be seen from saving time and money in the case registration process, as well as well-archived documents, accessible from various locations and media as well as a faster data retrieval process.